Corrosion resistance of FeCrAl coatings on Mo–La alloys - XI Sha; AN Geng; ZHANG Xiao; ZHOU Sha; LIU Renzhi; WU Jina (Fenmo yejin jishu)
FeCrAl coatings were deposited on the surface of Mo–La alloys by the non-equilibrium magnetron sputtering process. The corrosion resistance and corrosion mechanism of the FeCrAl coatings were investigated. The results show that, the average corrosion rate of FeCrAl coatings is 3.8 mg·dm‒2 in the autoclave under 360 ℃, 18.6 MPa, and pure water corrosion condition for 72 h, which is lower than that of zirconium alloys and Mo–La alloys without coating. Al in the coating reacts with the oxygen in the environment medium, forming a dense Al2O3 film on the surface of the coatings, which slows down the corrosion rate of the coatings and effectively protects the substrate materials. The thickness of Al2O3 film is about 4 μm after the FeCrAl coatings are corroded for 8 h at 1200 ℃ and 0.1 MPa, the coatings maintain the protective effect, and the Mo–La alloy substrate is not exposed to the corrosion environment. After quenching, the thickness of Al2O3 film reduces to about 2.5 μm, the coatings keep the structural integrity, and there is no penetrating shedding in Mo–La alloy surface, which meets the requirement of corrosion resistance.